2021
DOI: 10.1039/d1cp01105g
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of a deep eutectic solvent: structural properties of choline chloride : sesamol 1 : 3 compared to reline

Abstract: The structural properties of the deep eutectic solvent (DES) formed by choline chloride (ChCl) and sesamol in 1:3 ratio have been investigated and compared to those of reline (ChCl:urea 1:2)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“… 36 , 37 All the stretching vibrations involving the hydrogen atoms were constrained with the LINCS algorithm. 38 The employed simulation protocol is reported elsewhere, 4 , 39 − 43 though details are provided in the SI .…”
Section: Methodsmentioning
confidence: 99%
“… 36 , 37 All the stretching vibrations involving the hydrogen atoms were constrained with the LINCS algorithm. 38 The employed simulation protocol is reported elsewhere, 4 , 39 − 43 though details are provided in the SI .…”
Section: Methodsmentioning
confidence: 99%
“…These bands were previously observed to be red-shifted with respect to the O−H absorption of the pure components, evidencing the formation of the eutectic through the establishment of strong HBs between the chloride anion with the choline cation and the sesamol molecule. 15,37 The additional spectral features at lower wavenumbers are assigned exclusively to the sesamol moiety, in particular the C=C stretching at 1610 cm −1 , the C−H bending region (1500−1300 cm −1 ), the strong C−O stretching absorption between 1300 and 1000 cm −1 , and the out-of-plane ring deformation (δ ring (sesamol)) at 765 cm −1 . 63 Unfortunately, bands related to ChCl only are too weak and unresolved to be employed in the analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This picture is in agreement with previous findings describing the structure of this eutectic as formed by discrete chloride clusters that see almost the entire amount of sesamol and choline molecules involved, packed to maximize the HB interactions. 36,37 When MeOH is added to the DES, the N value for the Cl−MeOH interaction (Figure 3a) between the chloride anion and the hydroxyl group of MeOH increases sharply with increasing MeOH concentration (Figure 3d). In detail, an average number of 1.3 MeOH molecules is found in the coordination sphere of the chloride anion for M = 2, while the chloride anion is coordinated by 3.7 MeOH molecules for M = 24.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of their components strongly influence all DESs’ physicochemical properties, such as melting point, density, conductivity, and viscosity [ 12 ]. Moreover, studies on the three-dimensional structure of DESs revealed that the interaction between HBDs and HBAs depends mainly on hydrogen bonds, but they also interact with the anion by arranging themselves around it [ 13 ]. In general, the presence of a broad hydrogen-bonding network among the components is responsible for the high viscosity of DESs and the restrained mobility of free species inside the solvent.…”
Section: Introductionmentioning
confidence: 99%